AN INTERVIEW WITH KRZYSZTOF PENDERECKI. (October 2020) - Woodman, Alexander
Abstract: This article transcribes an interview with the great Polish composer Krzysztof Penderecki and is one of the last interviews that Penderecki gave before his death on 29 March 2020. It traces the composer's career, from his early musical education to the Ninth Symphony on which he was working at the time of his death, and focuses on the composition of his Threnody for the Victims of Hiroshima, the St Luke Passion and the Polish Requiem.